Penyuluhan hukum dampak bullying pada siswa Madrasah Aliyah Khusnul Yaqin Pontianak Utara dan Madrasah Aliyah Pondok Pesantren Mambau Shofa Pontianak Timur - Yamani, M. Alamul Huda; Suryani, Suryani; Hadi, Abdul; Putra, Satria Mandala; Saputra, Andi; Ramadhan, Imran (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
Bullying itself is an aggressive act or manipulation that is conscious and purposeful carried out by one or more people against one or a group of other people. The bullying phenomenon that occurred at MA Khusnul Yaqin and MA Mambau Shofa schools is a phenomenon where many bullying acts are carried out unknowingly by students at the school. There is a need for legal counseling related to bullying acts by providing legal education and understanding about bullying. Perpetrators who feel that bullying is normal, both verbally and non-verbally, and for victims of bullying, awareness of legal protection can be provided so that victims of bullying feel protected and avoid the impact of bullying that can attack mental health. This counseling is carried out using a persuasive, educational, and communicative approach. Legal counseling about the impact of bullying is expected to raise awareness of teachers, students, and the general community around the importance of bullying counseling in the school environment because of the huge impact on student psychology and the very severe legal sanctions for perpetrators of bullying, especially in the school environment.